Repetitive mild traumatic brain injury-induced neurodegeneration and inflammation is attenuated by acetyl-L-carnitine in a preclinical model - Hiskens, Matthew I.; Li, Katy M.; Schneiders, Anthony G.; Fenning, Andrew S. (Frontiers in Pharmacology, 2023)
Repetitive mild traumatic brain injuries (rmTBI) may contribute to the development of neurodegenerative diseases through secondary injury pathways. Acetyl-L-carnitine (ALC) shows neuroprotection through anti-inflammatory effects and via regulation of neuronal synaptic plasticity by counteracting post-trauma excitotoxicity. This study aimed to investigate mechanisms implicated in the etiology of neurodegeneration in rmTBI mice treated with ALC. Adult male C57BL/6J mice were allocated to sham, rmTBI or ALC + rmTBI groups. 15 rmTBIs were administered across 23 days using a modified weight drop model. Neurological testing and spatial learning and memory assessments via the Morris Water Maze (MWM) were undertaken at 48 hours and three months. RT-PCR analysis of the cortex and hippocampus was undertaken for MAPT, GFAP, AIF1, GRIA, CCL11, TDP43, and TNF genes. Gene expression in the cortex showed elevated mRNA levels of MAPT, TNF, and GFAP in the rmTBI group that were reduced by ALC treatment. In the hippocampus, mRNA expression was elevated for GRIA1 in the rmTBI group but not the ALC + rmTBI treatment group. ALC treatment showed protective effects against the deficits displayed in neurological testing and MWM assessment observed in the rmTBI group. While brain structures display differential vulnerability to insult as evidenced by location specific postimpact disruption of key genes, this study shows correlative mRNA neurodegeneration and functional impairment that was ameliorated by ALC treatment in several key genes. ALC may mitigate damage inflicted in the various secondary neurodegenerative cascades and contribute to functional protection following rmTBI.